High density cell seeding affects the rheology and printability of collagen bioinks. (22nd August 2019) - Diamantides, Nicole; Dugopolski, Caroline; Blahut, Eric; Kennedy, Stephen; Bonassar, Lawrence J
Abstract: An advantage of bioprinting is the ability to incorporate cells into the hydrogel bioink allowing for precise control over cell placement within a construct. Previous work found that the printability of collagen bioinks is highly dependent on their rheological properties. The effect of cell density on collagen rheological properties and, therefore, printability has not been assessed. Therefore, the objective of this study was to determine the effects of incorporating cells on the rheology and printability of collagen bioinks. Primary chondrocytes, at densities relevant to cartilage tissue engineering (up to 100 × 10 6 cells ml −1 ), were incorporated into 8 mg ml −1 collagen bioinks. Bioink rheological properties before, during, and after gelation as well as printability were assessed. Cell-laden printed constructs were also cultured for up to 14 d to assess longer-term cell behavior. The addition of cells resulted in an increase in the storage modulus and viscosity of the collagen before gelation. However, the storage modulus after gelation and the rate of gelation decreased with increasing cell density. Theoretical models were compared to the rheological data to suggest frameworks that could be used to predict the rheological properties of cell-laden bioinks. Printability testing showed that improved printability could be achieved with higher cell densities. Fourteen-day culture studies showed that the printing process had no adverse effects on the viability or function of printed cells. Overall, this study shows that collagen bioinks are conducive to bioprinting with a wide range of cell densities while maintaining high printability and chondrocyte viability and function.